Non-spontaneous and communicative emotive interjections: – ecological pragmatic observations - Borchmann, Simon (Scandinavian Studies in Language, 2019)
The basic feature of emotive interjections is that they are spontaneous. This feature implies that they are not intentional and, hence, not communicative. Nevertheless, in addition to spontaneous and non-communicative emotive interjections one can observe emotive interjections that are non-spontaneous and communicative and emotive interjections that are spontaneous and communicative. This heterogeneity poses a fundamental problem for the classification and description of interjections, and it is this problem that is the focus of this article. Th e article presents an ecological pragmatic analysis of emotive interjections with special regard to the evaluation of four accounts of the heterogeneity. The article’s contribution consists of observation-based evidence in the form of an analysis of three occurrences of interjections that differ with regard to their spontaneity and communicativity. Th e article suggests that the basic sign relation of emotive interjections is indexical, but it also shows that an iconic and a symbolic relation can be added to this basic relation.